Adsorption of paraquat herbicide on deposits from drinking water networks - Mónica S. F. Santos (2013)
Although forbidden in Europe, paraquat is still largely used worldwide as herbicide. Therefore, the hypothesis of an accidental or deliberate contamination of drinking water distribution systems (DWDSs) may be posed. The interactions between paraquat and three typical deposits (S2, S3 and S4 deposits) from DWDS were investigated in order to understand the fate of this chemical in such systems in case of contamination. Additionally, these materials can be valorized as adsorbents in wastewater treatment applications. The effect of stirring speed, adsorbent dose, initial paraquat concentration and temperature on the adsorption kinetics was evaluated. Good adherence was observed between experimental data and both kinetic (pseudo-second order) and equilibrium (Langmuir) models. The interaction between paraquat and the deposits is extremely weak when compared to those established in the paraquat-clay system, where irreversible sorption was observed. It was found that S2 and S3 may represent potential adsorbents regarding the treatment of paraquat-contaminated waters.